Childhood fever in well-child clinics: a focus group study among doctors and nurses. Issue 1 (December 2016) - Peetoom, Kirsten; Ploum, Luc; Smits, Jacqueline; Halbach, Nicky; Dinant, Geert-Jan; Cals, Jochen
Abstract Background Fever is common in children aged 0-4 years old and often leads to parental worries and in turn, high use of healthcare services. Educating parents may have beneficial effects on their sense of coping and fever management. Most parents receive information when their child is ill but it might be more desirable to educate parents in the setting of well-child clinics prior to their child becoming ill, in order to prepare parents for future illness management. This study aims to explore experiences of well-child clinic professionals when dealing with childhood fever and current practices of fever information provision to identify starting points for future interventions. Methods We held four focus group discussions based on naturalistic enquiry among 22 well-child clinic professionals. Data was analysed using the constant comparative technique. Results Well-child clinic professionals regularly received questions from parents about childhood fever and felt that parental worries were the major driving factor behind these contacts. These worries were assumed to be driven by: (1) lack of knowledge (2) experiences with fever (3) educational level and size social network (4) inconsistencies in paracetamol administration advice among healthcare professionals. Well-child clinic professionals perceive current information provision as limited and stated a need for improvement. For example, information should be consistent, easy to find and understand. Conclusions Fever-related questions are common in well-child care and professionals perceive that most of the workload is driven by parental worries. The focus group discussions revealed a desire to optimise the current limited information provision for childhood fever. Future interventions aimed at improving information provision for fever in well-child clinics should consider parental level of knowledge, experience, educational level and social network and inconsistencies among healthcare providers. Future fever information provision should focus on improving fever management and practical skills.